#TITLE_ALTERNATIVE# - KUSWANTO (NIM 13204094), ADI
3GPP have deployed seven frequency channels ex-AMPS band A as a valid channel to be used for spread spectrum 1 CDMA. In Indonesia those channels have been used by two service providers, with every service providers has been deployed by three channels and one channels between them (4th channel) as guard band. This research focused to evaluate the impact of the system, if 4th channel used by one of service provider. Another problem arises when those service providers operate the same frequency channels (impact of one of service provider moved from 1900 MHz frequency license) with geographic restriction. This research based on measurement of system quality, in the impact of interference from adjacent channel, especially result of interference as loss capacity in victim system. With the standard specification Base Station and Mobile Station, the simulations have been done to anticipate the interference, so the system is considered to be used together. The needs of guard band and how many guard band is needed one of the parameter as the result of simulation. In the boundary area (two service providers used same frequency) simulation have been done to achive minimum separation distance between two Base Station and the influence of power transmit in boundary areas. As the result, the simulations show that between two adjacent frequency channels that were operated by two service provider, need guard band not less than 0.1 MHz On cofrequency system in boundary area need minimum separation distance between two Base Station (each providers operate the similar BS, same transmit power and radius coverage) not less than 1.4 radius length. Or need to adjust the configuration of two Base Station so the power transmit that would be felt by mobile station in boundary area relative similar.